Mechanical Characterization of Methanol Plasma Treated Fluorocarbon Ultrathin Films Through Atomic Force Microscopy - Reggente, Melania; Angeloni, Livia; Passeri, Daniele; Chevallier, Pascale; Turgeon, Stephane; Mantovani, Diego; Rossi, Marco (Frontiers in Materials, 2020)
Methanol plasma has been proposed as an effective way to improve the performances of fluorocarbon (CFx) ultrathin films as stent coatings as it can successfully modulate fluorine content and wettability of the films. Nevertheless, plasma treatment may affect mechanical properties of the films, which therefore need comprehensively characterizing to verify the suitability of treated films for application as stent coating materials. In this work we investigate mechanical properties of methanol plasma treated CFx ultrathin films on stainless steel. In particular, cohesion of the films and their adhesion to the substrate is investigated using small punch test combined with atomic force microscopy (AFM) imaging. Also, elastic and viscoelastic properties are investigated at the nanometer scale using two different AFM based advanced technique for nanomechanical characterization, i.e., HarmoniXTM and contact resonance AFM (CR-AFM). Overall, methanol plasma treated CFx films have been demonstrated to be suitable for application as stent coating also on the basis of their nanomechanical properties.